Ativismo judicial na sociedade contemporânea: entre o dissenso democrático e os grupos de pressão - Scaff, Fabio Henrique (2024)
Our objective was to understand the increase in judicial protagonism arising from the strategy of parliamentarians, as well as pressure groups, which, defeated in the competent arena, seek by provoking the Judiciary, a second round in the debate, motivated by varied interests, which have as a backdrop In essence, the finding of identity bias on the part of judges. The posture of both the sender and the provoked recipient was analyzed in order to understand how this active action by the Judiciary reflects the separation of powers and, consequently, legitimacy. Respect for the law was praised as an element of legitimacy and support for democracy. We argue that, at the limit, when discretion would become excessive, only the legislator has the authority to create the legal text that fulfills the promise made in the past and resolves the problem situation that proves necessary. We always aim, within the boundaries of the Program, to observe solutions that lead to the effectiveness of the Law – since - without this - social conflict only tends to increase